2018
DOI: 10.1104/pp.18.00327
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Leaf Flatness Is Regulated by PPD2 and NINJA through Repression of CYCLIN D3 Genes

Abstract: In Arabidopsis (), reduced expression of the transcriptional regulator () results in propeller-like rosettes with enlarged and dome-shaped leaves. However, the molecular and cellular processes underlying this peculiar phenotype remain elusive. Here, we studied the interaction between PPD2 and NOVEL INTERACTOR OF JAZ (NINJA) and demonstrated that loss-of-function plants produce rosettes with dome-shaped leaves similar to those of mutants but without the increase in size. We showed that mutants have a convex-sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 62 publications
1
87
0
Order By: Relevance
“…PPD proteins have been reported to interact with the adaptor proteins KIX8/9 and NINJA to recruit TPL, generating a transcriptional repressor complex (Gonzalez et al 2015; Baekelandt et al 2018). TPL and TPL‐RELATED (TPR) belong to the family of Groucho/TUP1 transcriptional corepressors, and interact with a wide range of transcription factors to repress target gene expression (Causier et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPD proteins have been reported to interact with the adaptor proteins KIX8/9 and NINJA to recruit TPL, generating a transcriptional repressor complex (Gonzalez et al 2015; Baekelandt et al 2018). TPL and TPL‐RELATED (TPR) belong to the family of Groucho/TUP1 transcriptional corepressors, and interact with a wide range of transcription factors to repress target gene expression (Causier et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Li et al (2018) reported that the KIX‐PPD repressor complex was degraded by the F‐box protein STERILE APETALA (SAP). PPD2 was also identified to interact with NOVEL INTERACTOR OF JAZ (NINJA) to regulate leaf flatness via repressing expression of CYCD3 genes (Baekelandt et al 2018). Here, we report that LHP1 is a new PPD‐interacting partner and is enriched in the H3K27me3 regions of a set of cell cycle genes together with PPDs.…”
Section: Introductionmentioning
confidence: 99%
“…Our global profiling experiments also revealed multilayered plant-specific pathways that coordinate cell cycle progression. PEAPOD2 (PPD2) is a member of the TIFY transcription factor family that represses transcription of CycD3;2 to stop cell cycle progression (Baekelandt et al, 2018), which is required for patterning the leaf lamina (White, 2006). Although they act antagonistically, PPD2 and CycD3;2 were both identified in our analyses as 5′TOP mRNAs regulated by TOR-LARP1 signaling.…”
Section: Multilayered Regulation Of Plant Cell Cycle Progression By Tormentioning
confidence: 85%
“…Likewise, the fresh weight of the terminal leaflets of these kix8 kix9 leaves was increased with approximately 40% compared with those of wild-type leaves ( Figure 3b). Next, the area of terminal leaflets was measured before (projected area) and after (real area) terminal leaflets were cut to flatten them (Figure 3c,d) (Baekelandt et al, 2018). After flattening the terminal leaflets, those of kix8 kix9 mutants displayed an area that was approximately 1.4-fold larger than corresponding wild-type leaflets (Figure 3e).…”
Section: Crispr-cas9 Genome Editing Of Tomato Kix8 and Kix9 Leads Tomentioning
confidence: 99%
“…In Arabidopsis, KIX8 and KIX9 can interact with both PPD1 and PPD2 (Gonzalez et al, 2015). The PPD proteins, together with TIFY8 and the JASMONATE ZIM DOMAIN (JAZ) proteins, belong to class II of the TIFY protein family (Bai et al, 2011;Vanholme et al, 2007) Figure S1a) (Baekelandt et al, 2018;Chini et al, 2009;Chung and Howe, 2009;Pauwels et al, 2010). In contrast to class I members, class II proteins do not harbor a C2C2-GATA protein domain, but all of them, except TIFY8, do contain a C-terminal Jas domain (Bai et al, 2011;Vanholme et al, 2007).…”
Section: Introductionmentioning
confidence: 99%